Three-axis L1 adaptive attitude control of spacecraft using solar radiation pressure. (March 2015) - Lee, Keum W; Singh, Sahjendra N
Based on theL 1 adaptive control theory, a novel three-axis attitude control system for an axisymmetric spacecraft with uncertain dynamics moving in elliptic orbits, using solar radiation pressure, is derived. The nonaffine-in-control nonlinear spacecraft model includes the gravity gradient torque, the control torque produced by four solar flaps, and external time-varying disturbance moments. For the three-axis attitude control, anL 1 adaptive control system is designed, which includes a state predictor. A smooth projection algorithm is used to confine the estimated parameters within a desirable set. In the closed-loop system, the designed adaptive law accomplishes three-dimensional attitude control. A special feature of the attitude control system is that it is possible to select large adaptation gains for fast adaptation and to obtain quantifiable performance bounds. Simulation results show that in the closed-loop system, precise roll, yaw, and pitch angle control is accomplished, despite unmodeled nonlinearities, parameter uncertainty, and external disturbance inputs in the model.